2009
DOI: 10.3109/13550280903350200
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A deficiency and behavioral and motor deficits in the human immunodeficiency virus type 1 transgenic rat

Abstract: The HIV-1 Tg rat model incorporates a non-infectious viral genome that is under similar regulatory control mechanisms in vivo as those that exist with natural infection in humans. Vitamin A (VA) deficiency in humans has been associated with progressive systemic HIV disease and with impaired cognition in rodent models. The effects on of VA deficiency on the development of behavioral abnormalities with HIV infection have not been previously described. In these studies wild type (Wt) and transgenic (Tg) rats main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 50 publications
(59 reference statements)
3
14
0
Order By: Relevance
“…The lower locomotor activity and altered exploratory behavior of the HIV-1Tg rats is not caused by reduced motor competence because, in a rotarod test of balance and coordination, HIV-1Tg rats perform as well as control animals during initial training; although, in more challenging tests (faster rod rotation rates), performance is poorer than controls (June 2009). These results suggest good basic motor competence, but deficits in more complex tasks that may involve motor planning, a neurocognitive deficit characteristic of neuroHIV.…”
Section: Behavioral Alterations In the Hiv-1tg Ratmentioning
confidence: 91%
See 1 more Smart Citation
“…The lower locomotor activity and altered exploratory behavior of the HIV-1Tg rats is not caused by reduced motor competence because, in a rotarod test of balance and coordination, HIV-1Tg rats perform as well as control animals during initial training; although, in more challenging tests (faster rod rotation rates), performance is poorer than controls (June 2009). These results suggest good basic motor competence, but deficits in more complex tasks that may involve motor planning, a neurocognitive deficit characteristic of neuroHIV.…”
Section: Behavioral Alterations In the Hiv-1tg Ratmentioning
confidence: 91%
“…When tested using an open-field test, a common assessment of general locomotor activity, unconditioned motivated behavior, and behavioral plasticity (Walsh and Cummins 1976), HIV-1Tg rats demonstrate robust locomotor activity, but somewhat less overall activity than F344 controls (June 2009; Midde 2011; Moran, Booze et al 2013; Nemeth, Glasper et al 2014). Similar changes in open field behavior have also been noted in transgenic mice expressing gp120 (D’Hooge 1999).…”
Section: Behavioral Alterations In the Hiv-1tg Ratmentioning
confidence: 99%
“…The HIV transgenic rat, which incorporates a non-infectious HIV genome, has been shown to develop neurological abnormalities that are similar to those observed with natural HIV-1 infection in humans (Basselin et al, 2011; June et al, 2009; Liu et al, 2009; Peng et al, 2010; Reid et al, 2001; Royal, III et al, 2007; Sultana et al, 2010; Webb et al, 2010). In particular, the animals develop cognitive, behavioral and motor abnormalities which may be linked to the presence of increased systemic immune activation and loss of specific neuronal populations in the brain (June et al, 2009; Mazzucchelli et al, 2004; Royal, III et al, 2007). It has also been previously demonstrated that monocyte/macrophages from TG rats can efficiently transcribe HIV genes and can specifically express env and tat transcripts (Mazzucchelli et al, 2004).…”
Section: Introductionmentioning
confidence: 91%
“…The model mimics a number of abnormalities that have been demonstrated in humans with HIV infection. As we and others have previously demonstrated, these animals show evidence of (1) an increased proinflammatory state in brain and in peripheral immune cells (Cho et al 2017; Gorantla et al 2012; Royal et al 2012); (2) expression of HIV proteins in macrophage/microglial cells and astrocytes in the brain with envelope glycoprotein and tat expressed in the macrophage/microglial cells (Royal et al 2012), a pattern that is observed with HIV-1 infection in humans (Brack-Werner 1999; Glass et al 1995); (3) neurodegenerative effects characterized by decreased numbers of frontal cortex parvalbumin + neurons (Sultana et al 2010); and (4) the development of behavioral and motor abnormalities (June et al 2009; Moran et al 2013), all which are also observed in human HIV infection (Chana et al 2006). …”
Section: Discussionmentioning
confidence: 99%